Yağma suçu (TCK m. 148-150) - Şenerdoğan, Büşra (My University, 2017)
ÖZETTezimizin konusunu oluşturan yağma suçu, 5237 sayılı Türk Ceza Kanunu’nun “Özel Hükümler” başlıklı ikinci kitabının “Kişilere Karşı Suçlar” isimli ikinci kısmının “Malvarlığına Karşı Suçlar” şeklindeki onuncu bölümünde düzenlenmiştir.

ABSTRACTCrime of plunder which constitutes the subject of the thesis, was organized in the tenth part of the second part of the second book entitled Special Provisions of the Turkish Criminal Code numbered 5237, titled Crimes Against Property of the second part named Crimes Against Persons.
Keywords: Cebir; Coercion; Crimes Against Property; Hırsızlık; Kamu hukuku; Malvarlığına karşı suçlar; Plunder; Tehdit; Theft; Threat; Türkiye; Yağma